Implementing and documenting cultural adaption of evidence-based practice strategies to reduce opioid overdose deaths: examples and lessons from the HEALing communities study - Erin B. Gibson; LaShawn Glasgow; Monica Nouvong; Margaret McGladrey; Darcy Freedman; Deborah Chassler; Rachel Vickers-Smith; Madeline D’Onfro; Dawn A. Goddard-Eckrich; Timothy Hunt; Avik Chatterjee; JaNae Holloway; et al. (Discover Public Health)
Abstract Introduction Addressing the opioid overdose crisis requires developing contextually specific strategies promoting the adoption of evidence-based practices (EBPs) to prevent and treat opioid use disorder (OUD), including overdose education and naloxone distribution (OEND) and medications for OUD (MOUD). To effectively reach the groups most affected by the opioid crisis, EBP strategies must be adjusted to fit the culture and contexts of different communities. Methods The HEALing Communities Study engaged coalitions in 67 communities across four states to select and implement EBP strategies to reduce opioid overdose mortality. Coalitions were encouraged to culturally adapt EBP strategies for “special populations,” which were defined as groups that are highly impacted by OUD and face unique challenges in accessing prevention and treatment services. EBP strategies, and any efforts to culturally adapt them, were documented in coalition action plans. We collected quantitative and qualitative details from coalitions’ action plans. Following the first wave of the intervention (January 2020 – June 2022), we utilized the DATA (Describe, Analyze, Theorize, and ACT) model to evaluate the HEALing Communities Study approach to reaching special populations and identify areas for improvement. Finally, we identified variations across states in how cultural adaptation was interpreted and implemented. We provide strategies to improve how cultural adaption strategies are developed, documented, implemented, and monitored in future studies. Results Coalitions selected and implemented a variety of culturally tailored EBP strategies. However, complete understanding of the nature and effectiveness of cultural adaptation was limited by varying interpretations of what counts as cultural adaptation, inconsistent use of reporting guidance across research sites, and lack of data on the reach of each EBP strategy. Examples of cultural adaptation that successfully reached special populations included locating EBP strategies near each other to reduce transportation barriers, funding community-based organizations to help unhoused individuals meet basic needs, and hiring a bilingual and bicultural workforce to support prevention and treatment for OUD. Future studies should improve reporting of intersectional identities, measure EBP strategies’ reach, utilize real-world evidence of successful implementation strategies for cultural adaptation, and incorporate qualitative methods to contextualize cultural adaptation at local levels. Conclusion We call on funders, researchers, evaluators, and implementers to invest in training and technical assistance, robust documentation and monitoring protocols, and thoughtful community engagement to support cultural adaptation of EBP strategies to reduce overdose for the most vulnerable populations. Trial registration: ClinicalTrials.gov Identifier: NCT04111939. Date of registration 10/01/2019.